(untitled) (GEON Journal (Management, Organizations and Business), 2015)
The objective of this research is focused on studying the social and cultural meanings that mediate multi-sensory experience of taste with respect to consumption of food brands considering an interdisciplinary understanding from consumer psychology, anthropology consumer and marketing. In regard to the above it has been evident that the most intense multisensory experiences are linked to individual differences of consumers in terms of cultural and associated social variables, also what it is specific to a culture based on their food idiosyncrasy, much depends on the personal experience with the products, the formation of habits and learning in place in the family (Dalton and Clbs, 2000), reference groups and the media, in this sense food brands come with symbolism, with strong tendency to tribalism and individual preference formation within a socio-cultural context.